The Stoic Tradition - John Sellars (Elpis)
When we think about ancient philosophy we tend to think first and foremost of Plato and Aristotle, the two great Athenian philosophers, whose works have come down to us and that we can read today. In both cases the survival of their texts has been intertwined with commentary traditions, which could only come about because the texts were available but which also contributed to their survival for subsequent generations. The Neoplatonic practice of writing commentaries on the works of both Plato and Aristotle in late antiquity was central, laying the foundations for the subsequent philosophical traditions in Greek, Arabic, and Latin during the Middle Ages.